Informática na educação matemática : uma experiência com um grupo de professores da Rede Municipal de Ensino de Passo Fundo - Siveris, Marinez (2008)
For the use of technological resources, particularly those of computer laboratories in schools operated in its full potential and can bring significant gains to the process of teaching and learning, it is necessary to invest in projects of continuing education for teachers Coordinators of these laboratories. Thus, these coordinators will be able to take ownership of technological resources by using them in the rediscovery of a practical pedagogical approach that allows the content studied in school with the reality experienced by students and, most importantly, act as disseminators of this process to other teachers. Among the problems of learning in school, the math has been identified as a cause of difficulties for students, teachers and the school. This study presents an analysis of the continuing education of teachers coordinators laboratory of computer science qualification for the teaching of mathematics in contact with that environment. The study was conducted on the basis of current information technology to education, offered by the Municipal Department of Education of Passo Fundo, to a group of teachers that the municipal system of education, taught by the coordinator of the course, with the use of technological resources. Vygotsky, Piaget, Carraher, Fazenda and Japiassu form the basis of theoretical work, along with authors as well as other Valente, which address the issue of information technology education and educational issues in general. The object of study is of course that is explored educational games, resources, technological, mathematical concepts, enabling the development of educational projects. The analysis was performed using a qualitative approach, using observations of individual shares, the shares of small and the community, and the data obtained by the use of tools applied to all participants in the research. Through this study, it was possible to see that information technology is an important tool for mathematics education because, as a means of articulating human thought appears able to mobilize and assist in the development of mathematical concepts